The correlation between the dialogic parental guidance and the intensity of gadget utilization with the development of speaking and linguistic aspect of children at Tadika Puri early childhood education in 2018 - Winingsih, Gusti Ayu Martha (International Journal of Research in Medical Sciences, 2019)
Background :Since child development potentially subjects to disorder or deviation, early screening using the Pre-Screening Developmental Questionnaire must be conducted. The research result of Mardina (2016) shows that 8.2% toddlers experience suspect during their speech development. The introduction to gadget which happens too early and the absence of time limit could bring negative impact. Dialogic guidance from parents is highly needed to minimize the negative impact(s) of gadget utilization. This research aims to find the correlation between the dialogic parental guidance and the intensity of gadget utilization with the development of speech and linguistic on early childhood. Methods :The research design was analytical reseach with cross-sectional arrangement and quantitative approach. It was conducted at Tadika Puri Kindergarten. The size of sample was 35 people with purposive sampling technique. The instruments used were questionnaire and pre-screening developmental questionnaire (PDQ). The data analysis technique used was chi square and logistic regression test. Results :Based on the research results, the majority of 25 respondents (71.4%) received good parental guidance, almost half or 10 respondents (28.6 %) had high-intensity of gadget utilization, while the other half i.e. 11 respondents. (31.4%) experienced late development in speech and linguistic aspect. P value (0.02) < 0.05, there is correlation between dialogic parental guidance with speech development. P value (0.03) < 0.05 meant that there is correlation between the intensity and the linguistic development. Regression test, p value: = 0.018 < 0.05 , OR =4,307 which meant that intensity has special correlation and has opportunity which is 4 times bigger than dialogic parental guidance. Conclusion :There is correlation between dialogic guidance and the intensity of gadget utilization on the development of speech and linguistic.